Assessing the commutability of reference material formats for the harmonization of amyloid-? measurements - Bjerke, Maria; Andreasson, Ulf; Kuhlmann, Julia; Portelius, Erik; Pannee, Josef; Lewczuk, Piotr; Umek, Robert M.; Vanmechelen, Eugeen; Vanderstichele, Hugo; Stoops, Erik; Lewis, Jennifer; Vandijck, Manu; et al. (Clinical Chemistry and Laboratory Medicine, 2016)
The cerebrospinal fluid (CSF) amyloid-? (A?42) peptide is an important biomarker for Alzheimer's disease (AD). Variability in measured A?42 concentrations at different laboratories may be overcome by standardization and establishing traceability to a reference system. Candidate certified reference materials (CRMs) are validated herein for this purpose.Commutability of 16 candidate CRM formats was assessed across five CSF A?42 immunoassays and one mass spectrometry (MS) method in a set of 48 individual clinical CSF samples. Promising candidate CRM formats (neat CSF and CSF spiked with A?42) were identified and subjected to validation across eight (Elecsys, EUROIMMUN, IBL, INNO-BIA AlzBio3, INNOTEST, MSD, Simoa, and Saladax) immunoassays and the MS method in 32 individual CSF samples. Commutability was evaluated by Passing-Bablok regression and the candidate CRM termed commutable when found within the prediction interval (PI). The relative distance to the regression line was assessed.The neat CSF candidate CRM format was commutable for almost all method comparisons, except for the Simoa/MSD, Simoa/MS and MS/IBL where it was found just outside the 95% PI. However, the neat CSF was found within 5% relative distance to the regression line for MS/IBL, between 5% and 10% for Simoa/MS and between 10% and 15% for Simoa/MSD comparisons.The neat CSF candidate CRM format was commutable for 33 of 36 method comparisons, only one comparison more than expected given the 95% PI acceptance limit. We conclude that the neat CSF candidate CRM can be used for value assignment of the kit calibrators for the different A?42 methods.
EVALuna2:23763